2001
DOI: 10.1093/treephys/21.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Internal leaf anatomy and photosynthetic resource-use efficiency: interspecific and intraspecific comparisons

Abstract: Leaf mass per unit area (LMA) and internal leaf anatomy often affect net gas exchange because of their effects on internal CO2 conductance to the site of carboxylation, internal shading, competition for CO2 among carboxylation sites, nitrogen concentration and its partitioning. To evaluate effects of LMA and leaf anatomy on CO2 assimilation, water-use efficiency (WUE) and nitrogen-use efficiency (NUE), we measured LMA, leaf thickness, the thickness of mesophyll components, and gas exchange rates at ambient CO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
90
1
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 32 publications
10
90
1
5
Order By: Relevance
“…As a consequence, in the seedlings the interspecific differences differed from those we and many other authors have observed in mature trees. Thus, in the mature trees, a lower stomatal conductance and assimilation rate was associated with a longer leaf life span, greater LMA and smaller N mass , as several authors have reported [21,25,27]. By contrast, among the seedlings, neither the interspecific differences in the maximum stomatal conductance nor in the photosynthetic rates can be fully explained by the leaf life span, although PNUE was still clearly lower in Q. ilex seedlings than in the two deciduous species, owing to the effects associated with the greater LMA [23].…”
Section: Discussionsupporting
confidence: 55%
“…As a consequence, in the seedlings the interspecific differences differed from those we and many other authors have observed in mature trees. Thus, in the mature trees, a lower stomatal conductance and assimilation rate was associated with a longer leaf life span, greater LMA and smaller N mass , as several authors have reported [21,25,27]. By contrast, among the seedlings, neither the interspecific differences in the maximum stomatal conductance nor in the photosynthetic rates can be fully explained by the leaf life span, although PNUE was still clearly lower in Q. ilex seedlings than in the two deciduous species, owing to the effects associated with the greater LMA [23].…”
Section: Discussionsupporting
confidence: 55%
“…Changes in leaf anatomy alter the CO 2 conductance diffusion components from the substomatal cavities despite the low stomatal conductance to the sites of carboxylation contributing to the maintenance of photosynthetic rates (Chartzoulakis et al 1999). The WD induced high-density leaf tissue which produces a reduction in the volume fraction of intercellular spaces, diminishing the diffusion component of CO 2 conductance (Chartzoulakis et al 1999;Mediavilla et al 2001). D increase induced by WD is due to reductions in turgor pressure and cell expansion in the same dry mass within a smaller LA …”
mentioning
confidence: 99%
“…Accordingly, leaves with a high D survive a severe WD because of a higher resistance to physical damage by desiccation (Mediavilla et al 2001). In V cv, the slowness in the recovery of the sclerophylly indices may have induced and maintained the activation of Rubisco by prolonging the exposure of the enzyme to high concentration of CO 2 , favoring the activation and catalysis kinetics of carboxylase reaction of Rubisco.…”
mentioning
confidence: 99%
“…These modifications include dense stomata (Larcher 2003), longer roots with extensive branches (Passioura 1983, Arndt 2000, rolling leaf (Schwabe & Lionakis 1996), dense leaf pubescence (Karabourniotis & Bornman 1999, Liakoura et al 1999, Bacelar et al 2004, less intercellular space and smaller mesophyll cells (Bongi et al 1987, Mediavilla et al 2001, epicuticular wax layer and thick cuticle (Leon & Bukovac 1978) and lignified tissue (Richardson & Berlyn 2002). Root structure is associated with dehydration avoidance mechanisms.…”
Section: Key Plant Products and Common Mechanisms Utilized By Plants mentioning
confidence: 99%